2010
DOI: 10.1007/s00429-010-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

The sentient self

Abstract: This article addresses the neuroanatomical evidence for a progression of integrative representations of affective feelings from the body that lead to an ultimate representation of all feelings in the bilateral anterior insulae, or "the sentient self." Evidence for somatotopy in the primary interoceptive sensory cortex is presented, and the organization of the mid-insula and the anterior insula is discussed. Issues that need to be addressed are highlighted. A possible basis for subjectivity in a cinemascopic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
417
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(450 citation statements)
references
References 124 publications
(129 reference statements)
28
417
0
5
Order By: Relevance
“…We observed alterations in functional connectivity between the placebo and MDMA condition in many clusters overlapping with the HarvardOxford Atlas (Supplementary Information S1), notably including the right insular cortex (Figure 2a). All further analyses used the insula cluster revealed by the ICC as a seed ROI because it was selected by a prior application of the ICC (Martuzzi et al, 2011), decreased right insular connectivity was strikingly absent from previous fMRI analyses applied to this data set (Carhart-Harris et al, 2015;Roseman et al, 2014), and the insula plays a crucial role in both subjective feelings of the body (Craig, 2002;2009;2010;Critchley et al, 2004) and anxiety (Alvarez et al, 2015;Grupe and Nitschke, 2013;Paulus and Stein, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed alterations in functional connectivity between the placebo and MDMA condition in many clusters overlapping with the HarvardOxford Atlas (Supplementary Information S1), notably including the right insular cortex (Figure 2a). All further analyses used the insula cluster revealed by the ICC as a seed ROI because it was selected by a prior application of the ICC (Martuzzi et al, 2011), decreased right insular connectivity was strikingly absent from previous fMRI analyses applied to this data set (Carhart-Harris et al, 2015;Roseman et al, 2014), and the insula plays a crucial role in both subjective feelings of the body (Craig, 2002;2009;2010;Critchley et al, 2004) and anxiety (Alvarez et al, 2015;Grupe and Nitschke, 2013;Paulus and Stein, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Seeley et al, 2007, have previously demonstrated increased connectivity in the salience network (dACC and dorsolateral prefrontal cortex) in association with pre-scan anxiety, interpreted as evidence of trait anxiety coded to some degree in the functional architecture of the salience network (2007). Furthermore, alterations in insular functional connectivity following MDMA administration have never been explored despite converging evidence implicating a functional network anchored in the insula in subjective feelings of the body (Craig, 2002;2003;2009;2010; and anxiety (Alvarez et al, 2015;Grupe and Nitschke, 2013;Paulus and Stein, 2006;Seeley et al, 2007). As such, we endeavored to investigate how differences in right insula functional connectivity under MDMA (compared with placebo) might be related to individual differences in trait anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Projections from anterior insular cortex to ventral striato-pallidum and extended amygdala are thought to contribute to learned-and motivation-driven behaviors, especially those requiring emotional processing (28,29). Human imaging studies suggest that the anterior insula provides a rich interoceptive foundation within which emotionally salient activity from forebrain regions, including the orbitofrontal, dorsolateral prefrontal, and anterior cingulate cortices may be integrated (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that the anterior insula is involved in awareness (Ploran et al 2007;Nelson et al 2010;Craig 2010). This connection with awareness was initially suggested in an fMRI experiment by Kikyo and Ohki (2002) in which they observed activity in anterior insula when subjects reported the subjective sense of knowing a word before recalling it in a memory task, which these authors called the ''feeling of knowing''.…”
Section: Introductionmentioning
confidence: 99%